Granulometry sediment size analysis on sediment samples collected during Changing Arctic Ocean cruises JR16006, JR17007 and JR18006 in the Barents Sea - Ruhl, Saskia; Nunes, Joana; Coppock, Rachel; Mesher, Thomas (British Oceanographic Data Centre, National Oceanography Centre, NERC, UK, 2020)
Sediment grain size samples collected during a series of ship-board sampling campaigns in the Barents Sea, along a North-South transect at 30 degrees Longitude in July of 2017 (cruise JR16006), 2018 (cruise JR17007) and 2019 (cruise JR18006) as part of the Changing Arctic Ocean programme. Samples were collected using replicate USNL box cores, and sub-sampled with 50 ml syringe cores. Sample analysis was undertaken at a later date, using a Laser Coulter Sizer LS 130 micro volume model.